Developing Electrical System Analysis of Car Floor Vacuuming Robot Based on Dust Sensor - Yahya, Wachid; Sudiro, Sudiro; Bahtiar, Hafid; Supriyadi, Slamet; Muhamad, Wan Mansor Wan (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
This research addresses the increasing demand for automated cleaning solutions, particularly for vehicle interiors, where traditional manual cleaning methods often prove inefficient and time-consuming. The primary aim of this study is to develop an autonomous robot vacuum cleaner capable of cleaning the floor of a vehicle by detecting dust or dirt, using a proximity sensor to avoid obstacles, and operating based on input from a dust sensor. The research follows a systematic process, including topic selection, literature review, design challenges, system design, testing, and result analysis, to evaluate the performance and limitations of the proposed system. The results of this research indicate that the robot operates effectively, with optimal movement achieved when the battery voltage ranges between 12.2V and 10.9V. Below 10.9V, the robot’s movement becomes suboptimal. The 60W vacuum cleaner on the robot successfully collects debris such as paper pieces, tissue scraps, and fine soil particles. In conclusion, this car floor vacuuming robot, based on a dust sensor, demonstrates satisfactory functionality in terms of system performance, battery life, movement, and cleaning capability. The study suggests potential for further development, particularly in enhancing technical design and integrating advanced technologies such as autonomous navigation and the Internet of Things (IoT).